AMBIVALENSI KEHIDUPAN TOKOH LARASATI DALAM ROMAN LARASATI KARYA PRAMOEDYA ANANTA TOER: KAJIAN PASCAKOLONIALISME - Daratullaila Nasri (Madah: Jurnal Bahasa dan Sastra, 2016)
Larasati is a novel by Pramoedya Ananta Toer that records Indonesia’s flaming revolution at post-proclamation, not by “the great people and elders”, but a woman, Larasati. She was an ordinary villager whom became a stage artist and beautiful movie star as well as a woman who “prostitute herself to the colonialist”. This research uses post-colonialism theory and descriptive-analysis method. From the approachment used, the representation of ambivalency action from the live of the ruled ones can be seen.